Human Resources Management Audit to Assess the Performance of the Employees at PT Samator - Tsauri, Muh Sufyan; Rustam, Akie Rusaktiva (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
Human Resource is the most important resource to realize the company’s visions to optimize the potential of the human resource, a good management is needed including management policies such as procedures and systems application which is handled by Human Resource Division or Personnel Department which are responsible for getting, utilizing, and maintaining the human resource. Human Resource (HR) Management Audit is important in noticing the effectiveness and the efficiency of the whole function of HR in managing human resources of a company. PT Samator has competent human resources in the field. Because companies want to provide the best kind of stakeholders, is committed to product quality, improve services and customer solution orientation, the functions, duties and responsibilities of the HR can be judged effective or through a performance audit of human resources management. The type research is a case study with descriptive method that the problem characteristic related to the background of the study with the recent condition and also observes the subject interaction with the environment around. The research focused on performance scoring towards the employee of PT Samator which includes human resources recruitment, orientation, and placing, employee training and development, employees’ work achievement scoring, employees’ performance evaluation, carrier training and development, allowance giving, maintenance of relation between employee and separation and retirement. Of the nine human resource audit functions has been operating effectively. And of the development of criteria, causes, effects of each function in each department, discovered a weaknesses that the company still has not done an employee satisfaction survey as an evaluation and feedback for the formulation of the HR plan the next period.